2015
DOI: 10.1007/s11999-015-4191-3
|View full text |Cite
|
Sign up to set email alerts
|

Twenty Percent of Patients May Remain Colonized With Methicillin-resistant Staphylococcus aureus Despite a Decolonization Protocol in Patients Undergoing Elective Total Joint Arthroplasty

Abstract: Background Staphylococcus aureus is the most commonly isolated organism in periprosthetic joint infection (PJI). Resistant strains such as methicillin-resistant S aureus (MRSA) are on the rise, and many programs have instituted decolonization protocols. There are limited data on the success of S aureus nasal decolonization programs and their impact on PJI. Questions/purposes The purposes of this study were to (1) determine the proportion of patients successfully decolonized using a 2-week protocol; (2) compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
44
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(46 citation statements)
references
References 34 publications
0
44
1
Order By: Relevance
“…Even so, we believe that our study could provide some information on current treatment of PJI. Previous studies have found that decolonization plays an essential role in postoperative infection, and the use of prophylactic antibiotics against the decolonization might decrease the rate of PJI. Further study should focus on finding common decolonizing bacterium in patients undertaking elective orthopaedic surgery in China, and further test the appropriateness of using cefuroxime and clindamycin in prophylaxis in primary TJA.…”
Section: Discussionmentioning
confidence: 99%
“…Even so, we believe that our study could provide some information on current treatment of PJI. Previous studies have found that decolonization plays an essential role in postoperative infection, and the use of prophylactic antibiotics against the decolonization might decrease the rate of PJI. Further study should focus on finding common decolonizing bacterium in patients undertaking elective orthopaedic surgery in China, and further test the appropriateness of using cefuroxime and clindamycin in prophylaxis in primary TJA.…”
Section: Discussionmentioning
confidence: 99%
“…All studies contributed to the meta-analysis. [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] Nine of the eligible studies 19,22,24,25,[27][28][29][30]35 included cardiac patients and nine 20,21,23,26,[31][32][33]36,37 included orthopaedic patients; the remaining studies included both types of patients. Two cardiac studies were on paediatric populations 19,25 and the remaining were all adults.…”
Section: Observational Studiesmentioning
confidence: 99%
“…Mupirocin (2% ointment) was used under different regimens by 18 studies, 19,20,[22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] and povidone-iodine was used in two studies as the nasal decolonization agent. 21,33 Chlorhexidine was used for skin decolonization in patients in the form of soaps for showering 19,20,[26][27][28][29]34,35,37 or wipes for skin cleansing. 21 Mouthwash using chlorhexidine was applied to patients in one study.…”
Section: Observational Studiesmentioning
confidence: 99%
“…27 However, literature still exists doubting the effectiveness of this treatment in prevention. 28-31 …”
Section: Pre-operative Factorsmentioning
confidence: 99%